Are there Opportunities for a Specialist Menopause Pharmacist in Libya? - Eman Elmahjoubi; Nabila Rghebi; Atia, Wadiaa Benamer; Mufida Yamane (AlQalam Journal of Medical and Applied Sciences, 2021)
Background and objectives: Menopause is the permanent cessation of menses following the loss of ovarian follicular activity. It occurs usually in women in the age range of 45-58 years. The focus of this study was to evaluate the knowledge of Libyan pharmacists about menopause, and its management. The other aim is to determine the attitude towards menopause and Hormone Replacement Therapy (HRT) among Libyan women. Materials and Methods: A prospective, structured face-to-face interview was conducted between November 2017 and February 2018. Two different questionnaires were designed; the first one was distributed to 100 women aged ≥ 44 years, and the second designed to pharmacists (n = 100) surveyed their knowledge, basic skills and treatment choices of menopause. All participants were selected randomly. Results: The results show that 54% of women experienced menopause at age 49 to 53 years, the most symptoms reported were irregular menstruation (89.65%) and hot flushes (71.26%). (22%) of menopausal women sought medical advice and used HRT. Pharmacists had basic knowledge about usage of combination of HRT but the majority are not aware about HRT interactions with food or with other diseases. Conclusions: The study highlighted the general awareness of the pharmacists about menopause and HRT, but sufficient knowledge on HRT interactions and effective communication skills were lacking.